n-cutting site of DNA splicing language for single string and palindromic rule - Nooradelena, Mohd Ruslim; Yuhani, Yusof; Noraziah, Adzhar (IOP Publishing, 2022)
A new symbolization of Yusof-Goode (Y-G) splicing system was introduced by Yusof in 2012, is inspired by the framework of Formal Language Theory introduced by Head in 1987. Y-G splicing system is intended to present the biological process of DNA splicing in a translucent way. In this paper, starting with some relevant preliminaries, one theorem is proposed via Y-G approach using one initial string and one rule with different characteristics of the restriction enzyme. Additionally, the theorem showed the behavior of the splicing languages generated at single stage splicing. Two cases are considered in the theorem by conducting splicing using palindromic rule and palindromic recognition site with same left and right context for Case I and different left and right context for Case II. Furthermore, two molecular examples are discussed to validate two cases proposed in the theorem, which shows the real meaning of the theorem in biological aspect. From the proposed theorem, based on the splicing language generated, the type of splicing language can be determined. It is discovered that, the generated languages are in the form of limit and transient.